Associations between age-related changes in bone microstructure and strength and dietary acid load in a cohort of community-dwelling, healthy men and postmenopausal women. Issue 4 (17th July 2020) - Papageorgiou, Maria; Merminod, Fanny; Chevalley, Thierry; van Rietbergen, Bert; Ferrari, Serge; Rizzoli, René; Biver, Emmanuel
ABSTRACT: Background: The importance of dietary acid load (DAL) in the pathogenesis of osteoporosis is still debated. Age-related changes in bone microstructure and strength in relation to DAL remain largely unexplored. Objectives: We investigated the associations between changes in areal and volumetric bone mineral density (BMD), bone microstructure and strength, fracture risk, and DAL in a prospective cohort of 65-y-old healthy men and postmenopausal women. Methods: Potential renal acid load (PRAL; mEq/d) was calculated as a DAL proxy to characterize participants' diet as alkaline (Alk-D; PRAL < −5), neutral (Neut-D; −5 ≤ PRAL ≤ 5), or acidic (Acid-D; PRAL >5). We measured areal BMD (aBMD) by DXA, and distal radius and tibia bone microstructure using high-resolution peripheral quantitative computed tomography, at baseline ( n  = 853) and after 6.1 ± 1.4 y ( n  = 708). Bone strength was estimated using finite element analyses at baseline and after 3.0 ± 0.5 y ( n  = 613). Prevalent and incident fractures were recorded. Results: The majority of the participants (59%) had an Alk-D, while 23% had a Neut-D, and 18% an Acid-D. Baseline aBMD and bone microstructure and strength did differ or were slightly better in women or men with an Acid-D versus those consuming an Alk-D or Neut-D. Indeed, women with an Acid-D had higher trabecular number ( P  = 0.010 vs. Alk-D; P  = 0.001 vs. Neut-D), while men had higher hip and radius aBMD ( P  = 0.008 and 0.024 vs. Neut-D, respectively) and radius strength ( P  = 0.026 vs. Neut-D). Over the follow-up, women in the Acid-D group experienced lower cortical and endocortical bone loss at the radius than did the Alk-D and Neut-D groups (cortical thickness, P  = 0.008 and < 0.001; trabecular area, P  = 0.001 and < 0.001, respectively). No association between fractures and PRAL was observed. Conclusions: These null or favourable associations between baseline values or changes in aBMD, bone microstructure and strength, and DAL in this cohort of 65-y-old healthy individuals do not support adverse DAL-mediated effects on bone. This trial was registered at http://www.isrctn.com as ISRCTN11865958.